The Influence of Ecological Factors on the Landscape Organization of Preschool Educational organizations - Mukhitdin Kizi, Musayeva Zumrad (European Journal of Life Safety and Stability (2660-9630), 2022)
In this state, basic attention is paid to urban planning issues, environmental issues, the distribution of educational organizations, the advantages and disadvantages, and the influence of environmental factors on the landscape of educational institutions in the city.